Hubungan Faktor Risiko Lingkungan Fisik dengan Kelelahan Tenaga Kerja di Industri Konveksi RM Tailor Yogyakarta - Pretty Bettyana Kusuma Wardani; Heru Subaris Kasjono; Yam Yamtana (Sanitasi: Jurnal Kesehatan Lingkungan, 2011)
Based on the reports of field study conducted in RM Tailor convection industry, in October-November 2009, the measurement of indoor light intensity was 72 lux, temperature was 38 oC and humidity was 58 %. It is well understood that physical factors which related with occupational environment affect workers’ fatigue, in that inadequate condition of physical factors increases the risk of getting fatigue. The aim of the study was to identify which environmental factors play as risk factors of fatigue among workers of the convection industry. The study was a cross sectional survey and was conducted on 24 April 2010 and involving 40 workers. The data obtained were processed by calculating the prevalence ratio (PR) to reveal the risk level and chi-square test at 95% significance level was used to know the relationship between two variables. The results showed that the prevalence ratios (PR) of illumination, temperature and humidity were 2,0; 1,9 and 1,6 respectively. The p-values obtained from chi-square test for the same parameters were 0,002; 0,032; and 0,033 res-pectively. Based on the results it can concluded that physical environment factors have relationship with workers’ fatigue, and light intensity is the strong-est risk factor.